1978
DOI: 10.1021/ac50030a026
|View full text |Cite
|
Sign up to set email alerts
|

Application of the method of rank annihilation to quantitative analyses of multicomponent fluorescence data from the video fluorometer

Abstract: A new scheme for quantitative analysis of a multicomponent fluorescent mixture using the Excitation-Emission Matrix (EEM) acquired by the video fluorometer has been developed and tested. This method, rank annihilation, Is capable of quantifying a particular component known to be present In the mixture without having also to know the Identity of the rest of the components. The theory of the method and the results of Its application to a mixture matrix are presented and comparison Is made with the method of leas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
99
0

Year Published

1981
1981
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 248 publications
(103 citation statements)
references
References 7 publications
0
99
0
Order By: Relevance
“…Excellent reviews and books exist on the matter. [12][13][14] Multi-way calibration is relatively new in this regard: the first work describing a secondorder calibration was published in 1978, 47 reporting the determination of polycyclic aromatic hydrocarbons in the presence of potential interfering agents. Then an impasse of ca.…”
mentioning
confidence: 99%
“…Excellent reviews and books exist on the matter. [12][13][14] Multi-way calibration is relatively new in this regard: the first work describing a secondorder calibration was published in 1978, 47 reporting the determination of polycyclic aromatic hydrocarbons in the presence of potential interfering agents. Then an impasse of ca.…”
mentioning
confidence: 99%
“…Rank annihilation factor analysis (RAFA) is an effective chemometric tool that the idea behind it, is the rank analysis of two way spectrum data, and quantitatively can be used to analysis of mix systems with unknown background. The original algorithm of RAFA was written by Ho et al and applied on one and two component mixtures of perylene and anthracene [20][21][22]. They showed that they were able to determine the concentration of one analyte in presence of the other using only one pure standard and using fluorescence excitation emission landscapes [23].…”
Section: Introductionmentioning
confidence: 99%
“…This property is the so-called "second-order advantage" 1 and it is based on the earlier work done in the psychometrics field. 2,3 The use of this advantage in analytical chemistry was proposed by Ho et al 4 (rank annihilation factor analysis, RAFA), for the multicomponent analysis of fluorescent mixtures using excitation-emission matrix (EEM). Later, Lorber 5 and Sanchez and Kowalski 6 proposed new and simple solutions for the method of Ho et al and now it is called the generalized rank annihilation method (GRAM).…”
Section: Introductionmentioning
confidence: 99%